Community Based Tourism Development Strategy Of Munggu Beach, Mengwi District, Badung Regency-Bali - Muter, Ida Ayu Made; Widanti, Ni Putu Tirka; Rai, Anak Agung Gede (Sean Institute, 2024)
Munggu beach community-based tourism development, the Government always includes the community in decision-making. Second, the management of beach tourism objects provides direct and indirect benefits to the community. Directly it can be felt by the community with an increase in the economy from beach tourism activities. Indirectly, the number of visitors who come to the beach tourism location can see and introduce the customs and customs of the local community. Third, involving managers, government and the community about good development procedures. Fourth, the government always gives space to the community to maintain its culture. Then the factors that support the development of community-based tourism are the natural beauty that is still maintained and also free tourist sites. Then the inhibiting factor is the lack of public awareness in maintaining environmental cleanliness and the absence of regulating regulations.